Penundaan Pembagian Warisan: Tradisi Menjaga Keharmonisan Keluarga Ditinjau Dari Sosiologi Hukum Islam Muhammad Artho' Mudzhar - Ridwan, Muhammad (Jurnal EL-QANUNIY: Jurnal Ilmu-Ilmu Kesyariahan dan Pranata Sosial, 2024)
This study aims to examine the delay in the distribution of heritage assets to the people of Padangsidimpuan. Interestingly, some people in Padangsidimpuan City want to divide the inheritance when both heirs have died, all heirs have been married, and the most share (portion) for the oldest child. Therefore, there are often delays in the distribution of inheritance because they do not find agreement between families.  This type of research is normative juridical legal research, while the data collection technique used is an interview with people who postpone the distribution of inheritance, namely the people of Padangsidimpuan. The results of this study show that the people of Padangsidimpuan City postponed the distribution of inheritance because they maintain the benefit of the family. This tradition has been valid for a long time, because the majority of the population adheres to the customary system (dalihan na tolu) which upholds the value of togetherness (ahwal). In addition, the fundamental reasons for delaying its implementation are that the heirs are not yet mature, no one has finished school, there is a biased assumption from the community when distributing inheritance (an heir dies) because they are considered greedy for inheritance.